Analisis Multivarian Terhadap Efektivitas Pembelajaran Daring pada Siswa di Sekolah Dasar Kelas Atas - Robiatul Adawiyah; Uswatun Hasanah; Aulia Kaffah Firdausi; Siti Lailiyah (Bidayatuna, 2022)
Online learning has its own challenges for teachers in order to achieve learning outcomes, especially in seeking children's character education as stated in the goals of character education. When learning is carried out online during the pandemic or face-to-face in this new normal era, there will certainly be differences in the implementation of activities, giving rise to various obstacles, especially related to the character of students' discipline and interest in learning. This study was to determine the effectiveness of online learning on upper grade elementary school students. This study also focuses on the character of discipline and interest in student learning in the upper class. This study uses the multivariate analysis technique MANOVA (Multivariate Analysis of Variance). The results of this study indicate that there is a significant difference in the character of students' discipline and interest during online learning and learning in the new normal era with a significance of 0.003 <0.05, which means that learning carried out in the new normal era is more effective than the character of discipline and interest. students during online learning during the covid-19 pandemic. This research is still not able to know the results of the conditions of students specifically so that it is still very necessary for materials and considerations for further research.